Remittances in Lebanon : A Dutch Disease or a Tool for Economic Growth? - Chhabra, Shreyus (2022)
The goal of this paper is to introduce remittances and how they can assist Lebanon, one of the top receivers of remittances in the world in absorbing economic shocks emerging from the ongoing financial and economic crisis. This paper shows that most of the Lebanese people vastly rely on remittances; it’s the main source of finance by which they can satisfy their basic daily needs. This strong dependence traps the Lebanese economy in a vicious trap because of which the economic sectors of Lebanon have been negatively affected, and the problem has been worsened after the 2019 financial crisis. Lebanon is facing a typical case of the Dutch Disease, the impact sectors were identified in this paper, which was the small and medium enterprises mainly and an impact on increasing brain drain from Lebanon. At the end of this paper, some recommendations were provided which might help Lebanon get out of this trap, one of them being Lebanese banks working with money transfer organisations to provide incentives plus legal and financial aid to aspiring Lebanese entrepreneurs, which can help uplift the Small and Medium-sized Enterprises and spur economic growth.